2018
DOI: 10.15226/2572-3154/3/2/00119
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Acceptance of Sweet Potato in Chips Format by Public School Students in Sertânia, Pernambuco, Brazil

Abstract: Thus, the objective of this study is to evaluate the sensory acceptance of sweet potato in "chips" format by adolescents in public schools, aiming at is commercialization in this consumer market. Sweet potato was peeled; cut was performed with the aid of multiprocessor foods (Metvisa) for obtaining the chips. Sensory analysis is based on nine-point hedonic scale ratings: 9 = like extremely and 1= dislike extremely. The tasters attributed notes for the attributes appearance, aroma, flavor and color. The sensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The results obtained in the sensorial analysis showed that the tasters had a good acceptance of the sweet potato chips, regardless of the sex of the tasters [11]. The only organoleptic characteristic that presented significant difference at the 5% probability level was the color attribute (Table 1).…”
Section: Sensory Analysismentioning
confidence: 91%
“…The results obtained in the sensorial analysis showed that the tasters had a good acceptance of the sweet potato chips, regardless of the sex of the tasters [11]. The only organoleptic characteristic that presented significant difference at the 5% probability level was the color attribute (Table 1).…”
Section: Sensory Analysismentioning
confidence: 91%